Examining the Role of Language, Culture and Communication Technology in Reconstructing Masculinity: A Reflection on Henry Ole Kulet’s To Become a Man - Mukasa, Antony; Kinanga, Charles (Machakos University, 2018)
This paper is an investigation on the role of language, culture and communication technology in reconstructing masculinity. The paper argues that there is an apparent disconnect between traditional and modern perspectives on what it means to be a man. The paper is guided by Raewyn Connell’s notion of masculinity. The paper seeks to examine the disconnect between the African traditional perception and the modern view of masculinity. It also analyses the role of language, culture and communication technology in the reconstruction of masculinity. The information in this paper was gathered through literature review. Among the key arguments in this paper is that there is an apparent disconnect between the traditional and modern views on what it means to be a man. The paper also argues that there is need to reconstruct the Aftican society’s perception of what it means to be a man in order to render it relevant in modern society. The paper further argues that language, culture and communication technology can play a complementary role in achieving this goal. Keywords: Masculinity, pre-modern, modern, femininity, partriarchal system, paradigm shift
Keywords: Masculinity; Femininity; Partriarchal system